Feeding Problems Including Avoidant Restrictive Food Intake Disorder in Young Children With Autism Spectrum Disorder in a Multiethnic Population - Nygren, Gudrun; Linnsand, Petra; Hermansson, Jonas; Dinkler, Lisa; Johansson, Maria; Gillberg, Christopher (Frontiers in Pediatrics, 2021)
We examined feeding problems, including Avoidant Restrictive Food Intake Disorder (ARFID), in preschool children with Autism Spectrum Disorder (ASD). Data were collected from a prospective longitudinal study of 46 children with ASD in a multiethnic, low resource area in Gothenburg, Sweden. Feeding problems were found in 76% of the children with ASD, and in 28%, the criteria for ARFID were met. The study highlights early onset age, the heterogeneity of feeding problems, and the need for multidisciplinary assessments in ASD as well as in feeding problems, and also the need for further elaboration of feeding disorder classifications in children.